2020
DOI: 10.7150/thno.45922
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Sirtuin 3: New emerging biological function and therapeutic target

Abstract: Sirtuin 3 (SIRT3) is one of the most prominent deacetylases that can regulate acetylation levels in mitochondria, which are essential for eukaryotic life and inextricably linked to the metabolism of multiple organs. Hitherto, SIRT3 has been substantiated to be involved in almost all aspects of mitochondrial metabolism and homeostasis, protecting mitochondria from a variety of damage. Accumulating evidence has recently documented that SIRT3 is associated with many types of human diseases, including age-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
260
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(263 citation statements)
references
References 200 publications
(237 reference statements)
3
260
0
Order By: Relevance
“…Increased acetylation of the ETC complexes correlates with a reduction in catalytic activity, impaired mitochondrial oxidative phosphorylation and consequently compromised contractile function of the heart. Therefore, approaches that upregulate and/or maintain SIRT3 expression and activity may represent a promising therapeutic strategy to treat or prevent cardiac dysfunction in the setting of MI [ 41 , 43 , 44 ]. In agreement with these reports, the current study demonstrated that the preserved SIRT3 activity in both sEH null mice or t AUCB pre-treated females subjected to MI correlates with enhanced cardiac contractile function compared to WT counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Increased acetylation of the ETC complexes correlates with a reduction in catalytic activity, impaired mitochondrial oxidative phosphorylation and consequently compromised contractile function of the heart. Therefore, approaches that upregulate and/or maintain SIRT3 expression and activity may represent a promising therapeutic strategy to treat or prevent cardiac dysfunction in the setting of MI [ 41 , 43 , 44 ]. In agreement with these reports, the current study demonstrated that the preserved SIRT3 activity in both sEH null mice or t AUCB pre-treated females subjected to MI correlates with enhanced cardiac contractile function compared to WT counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…CypD regulates the opening of mitochondrial permeability transition pore by phosphorylating serine residue S191 [ 25 ]. Indeed, SIRT3 which deacetylates CypD is downregulated in AD [ 26 ]. Furthermore, oAβ-CypD complexes were found in AD brains and transgenic AD mice [ 27 , 28 ].…”
Section: Brain Disorder and Mitochondrial Dysfunctionmentioning
confidence: 99%
“…NR1D1 is a key integrator of metabolism with the circadian clock and inhibits pro-inflammatory M1 macrophages and NLRP3 inflammasome activation ( 107 ). SIRT3 and PPAR-α play crucial roles in mitochondrial quality control, oxidative phosphorylation, and FAO in various cell types ( 108 , 109 ). Thus, TFEB, and its upstream signaling molecules, may orchestrate immunometabolism, autophagy, and the inflammatory response during Mtb infection.…”
Section: Tfeb: a Potential Coordinator Of Autophagy And Metabolism Dumentioning
confidence: 99%